Pengembangan Kegiatan Membatik dengan Bahan Alam Untuk Meningkatkan Kreativitas Anak Usia 5-6 Tahun - Baik Nilawati Astini; I Nyoman Suarta; Muazar Habibi; Yuli Fitrianingsih (Indonesian Journal of Elementary and Childhood Education, 2021)
This research is motivated by the low creativity of children aged 5-6 years in the Village Tarlawi of Bima regency. The formulation of the problem in this research is how the form of batik activities with natural materials and the way or the steps batik activities with natural materials to enhance the creativity of children aged 5-6 years. The purpose of this study is to determine the shape of batik activities as well as knowing how to or steps batik with natural ingredients to enhance the creativity of children aged 5-6 years in the Village Tarlawi of Bima regency. The type of this research is a development research with reference to the opinion of Borg & Gall. As for the number of subjects in this study is four people. Data were collected through observation method. Data analysis used is qualitative descriptive analysis. The study used a two-stage trial with four times the meeting. The results obtained in the test phase I (the meeting I) obtain the value of a percentage of (40,08%). an increase in the test phase I (II meeting) of (61,03%), in the test phase II (meeting III) increased again, reaching (67,28%), in the test phase II (meeting IV) by (83,09%). Conclusion the results of this study is the activity of making batik with natural materials can enhance the creativity of children aged 5-6 years after modification tools, materials and steps to make batik that will be done.